The effects of combined contrast heat cold pressure therapy on post-exercise muscle recovery in MMA fighters: A randomized controlled trial - Trybulski, R.; Zebrowska, A.; Bichowska-Paweska, M.; Kuzdzal, A.; Ryszkiel, I.; Silva, R. M.; Muracki, J.; Kawczynski, A. (Journal of Human Kinetics, 2024)
The purpose of this study was to evaluate the effects of contrast heat and cold pressure therapy (CHCP) on muscle tone, elasticity, stiffness, perfusion unit, and muscle fatigue indices after plyometric training consisting of five sets of jumping on a 50-cm high box until exhaustion. A prospective, randomized, controlled single-blind study design was used. Twenty professional MMA fighters were included in the study. The experimental group (n = 10) was subjected to the CHCP protocol (eGR), while the control group (cGR) (n = 10) was subjected to sham therapy. Both protocols consisted of three CHCP sessions performed immediately after plyometric exercise, 24 and 48 h afterwards. Measurements were taken at the following time points: 1) at rest; 2) 1 min post-exercise; 3) 1 min post-CHCP therapy; 4) 24 h post-CHCP therapy; 5) 48 h post-CHCP therapy. The results of the eGR compared to the cGR showed significantly higher perfusion at time point 5 (p < 0.001), higher muscle tone at time points 1, and 3-5 (p < 0.001 for all), higher stiffness at time points 1, 3-5 (p < 0.001 for all) and a higher pain threshold at time points 1 and 5 (p < 0.001 for all). This study suggests a positive effect of CHCP therapy on muscle biomechanics, the pain threshold, and tissue perfusion, which may contribute to increasing the effectiveness of post-exercise muscle recovery in MMA athletes.